DESIGNING ELMED (ENGLISH LISTENED MENTALLY DISABLE) MEDIA FOR STUDENT SMALB MUHAMMADIYAH JOMBANG - Agustina, Ulfa Wulan; Afidah, Nurul; Rohmah, Hidayatur (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2024)
Abstract The purpose of this research to improve English skills in listening for Students Mentally Disable and help student mentally disable in learning English. In this study, to design and develop application media based on ICT. This research was conducted on tenth grade students of SMALB Muhammadiyah Jombang.  This study researcher chooses listening as skill and used Research & Development (R&D) method which used ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The researcher used some instruments to collect data they are interview and questionnaires and use of data analysis techniques to calculate scores from questionnaires using Linkert scale techniques. The result of questionnaires from material validation was 92 % “Very good” category and the result of media validation was 91 % “Very good” category and while after being implemented to student the final result was 89% which was categorized as “Very good”. Based on those result, it can take conclude that ELMED (English Listened Mentally Disable) can help student mentally disable in learning English especially in listening skills